The Relationship Between Mother's Education Level and Family Welfare: A Case Study in Bandar Lampung City - Muhammad Farhan Barata; Dafa Epandi; Suci Nur Aisyah (Women, Education, and Social Welfare, 2024)
This study explores the relationship between maternal education level and family well-being in Bandar Lampung, a rapidly developing urban area in Indonesia. The research uses a descriptive quantitative approach, with data collected from 120 respondents through a questionnaire that measures various dimensions of family well-being, including economic status, access to healthcare and education, and overall quality of life. The findings reveal a moderate positive correlation between maternal education and family well-being (r = 0.61, p = 0.001), indicating that higher levels of maternal education significantly improve family welfare. Families with educated mothers report better economic conditions, greater access to healthcare and education, and a higher quality of life. These results highlight the crucial role of maternal education in enhancing family well-being, suggesting that improving education for women, particularly mothers, can have a profound impact on socio-economic development and reduce disparities. The study calls for policy interventions aimed at increasing educational access for women to foster long-term family and community welfare.